A rapid positioning method for high-purity quartz sand for photovoltaic quartz crucibles

CN122889164APending Publication Date: 2026-10-09ZHENGZHOU MINERALS COMPOSITIVE UTILIZATION RES INST CHINESE GEOLOGICAL ACAD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610897028.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-22
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0006]鉴于背景技术中提到的问题,本发明提供一种光伏石英坩埚用高纯石英砂的快速定位方法,旨在解决现有技术中验证高纯石英砂产品等级时存在验证成本高、时间长、效率低的问题

Benefits of technology

[0016] In this technical solution, the thickness of the transparent sheet should not be too thin or too thick. If it is too thin, it is easy to deform during polishing, resulting in the illusion of bubbles. If it is too thick, it will reduce the light transmittance and cover up the real defects. Through several experiments, this invention has confirmed that the thickness of the transparent sheet should be controlled at 2 mm, and the thickness deviation should be controlled within ±0.05 mm.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122889164A_ABST
    Figure CN122889164A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of high-purity quartz material application, and particularly discloses a rapid positioning method for high-purity quartz sand for photovoltaic quartz crucibles, which specifically comprises the following steps: S1, establishing a standard database of impurity elements, particle size distribution and inclusion characteristics of inner-layer sand, middle-layer sand and outer-layer sand for photovoltaic quartz crucibles, and preliminarily positioning the to-be-detected high-purity quartz sand by comparison; S2, melting the to-be-detected high-purity quartz sand into a glass body, comparing the transparency of the glass body with that of the glass bodies obtained by using standard inner-layer quartz sand, standard middle-layer quartz sand and standard outer-layer quartz sand, and positioning again; S3, melting the to-be-detected high-purity quartz sand into a quartz crucible with a size not less than 12 inches, and testing the bubble degree and the light transmittance; and S4, establishing a bubble degree and light transmittance database, and finally positioning by comparison. The application relates to the quality evaluation of a whole chain of raw materials, semi-finished products and products, is more comprehensive, objective and accurate, and more importantly, has low positioning cost, short positioning time and high efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of high-purity quartz material application technology, and specifically discloses a rapid positioning method for high-purity quartz sand used in photovoltaic quartz crucibles. Background Technology

[0002] High-purity quartz sand is produced from high-purity quartz ore, the 174th newly discovered mineral in my country, through beneficiation and purification processes. Its silica purity is no less than 99.99%, and its impurity, inclusion content, and particle size meet the requirements for applications in semiconductors, photovoltaics, and optics. High-purity quartz sand can be used to manufacture quartz glass products such as quartz tubes, quartz balls, quartz plates, and quartz crucibles. These products possess characteristics such as high temperature resistance, corrosion resistance, low thermal expansion, high thermal shock resistance, and high light transmittance, making them indispensable key materials for strategic emerging industries such as semiconductors and photovoltaics.

[0003] Quartz crucibles are primarily used in the Czochralski process for producing single-crystal silicon. During crystal growth, the quartz crucible is exposed for extended periods to high temperatures (1400-1600℃), high vacuum, or inert gas environments such as argon. The transparent layer of the quartz crucible is in direct contact with the molten silicon, therefore requiring extremely high purity and very few bubbles to prevent impurities and precipitated crystals from diffusing into the molten silicon. The bubble layer on the outside of the quartz crucible needs strong heat resistance and insulation at high temperatures. It must ensure the molten silicon is in a temperature-uniform thermal field, prevent bubbles from expanding and bursting and affecting the transparent layer, and prevent the quartz crucible from curling or collapsing. Therefore, the quality of the quartz crucible directly affects the yield and performance of Czochralski-grown single-crystal silicon.

[0004] High-purity quartz sand is the raw material for preparing quartz crucibles, and its quality directly determines the quality of the crucibles. However, the national standard GB / T 45823-2025, "High-purity Inner Layer Sand for Quartz Crucibles for Photovoltaic Monocrystalline Silicon Growth," only specifies the appearance, particle size, particle shape, loss on ignition, and impurity element content of quartz sand. In reality, simply meeting these conditions does not guarantee its suitability as inner layer sand for quartz crucibles. Currently, determining whether quartz sand is suitable for use as an inner layer requires producing a quartz crucible from approximately 100 kg of sample. The quality of the quartz sand is then determined by observing the transparent layer and conducting a crystal pulling time gradient test. This verification process requires a large amount of quartz sand, a significant experimental period, and substantial costs, resulting in a substantial waste of resources, time, and money.

[0005] Therefore, how to establish a rapid positioning method for high-purity quartz sand used in photovoltaic quartz crucibles to reduce verification costs, shorten verification time, and improve verification efficiency is a technical problem that urgently needs to be solved. Summary of the Invention

[0006] In view of the problems mentioned in the background art, the present invention provides a rapid positioning method for high-purity quartz sand for photovoltaic quartz crucibles, aiming to solve the problems of high verification cost, long time and low efficiency in the verification of high-purity quartz sand product grade in the prior art.

[0007] This invention is specifically achieved through the following technical solutions: A rapid positioning method for high-purity quartz sand used in photovoltaic quartz crucibles, the operation process of which is as follows: Figure 10 As shown: S1. Establish a standard database for three indicators: impurity elements, particle size distribution, and inclusion characteristics of the inner, middle, and outer layer sands used in photovoltaic quartz crucibles. Test these three indicators of the high-purity quartz sand to be tested. By comparing with the standard database, the position of the high-purity quartz sand to be tested can be preliminarily determined. If even the standard of the outer layer sand is not met, no further operation steps are required. Through S1, quality control is carried out at the raw material level so as to pre-screen a portion of better samples from a large number of samples. S2. Weigh an appropriate amount of the high-purity quartz sand to be tested and place it in a high-purity quartz glass tube. After evacuating the tube, ignite the high-purity quartz sand to be tested so that the bottom melts into a glass body. After cooling, observe the transparency of the glass body and compare it with the glass bodies obtained by igniting the standard inner layer quartz sand, standard middle layer quartz sand, and standard outer layer quartz sand respectively using the above method. Based on the principle of similar transparency, re-determine the position of the high-purity quartz sand to be tested. Among them, the standard inner layer quartz sand, standard middle layer quartz sand, and standard outer layer quartz sand are all commercially available. They can be the high-purity quartz sand for photovoltaic quartz crucibles currently on the market, such as the relevant products of the following manufacturers: Shaanxi Terai Crystal New Material Technology Co., Ltd., Anhui Weike Terui New Material Technology Co., Ltd., Jiangsu Pacific Quartz Co., Ltd., etc. Through the glass melting test of S2, quality control is carried out at the semi-finished product level. If the transparency of the sample is not as good as that of the standard outer layer of quartz sand, it is discarded and no further operation is required. The evaluation results of the glass melting test are stable. Multiple glass bodies melted from the same high-purity quartz sand have basically the same transparency as observed by the naked eye. There will be no situation where some are transparent and some are not. S3. Weigh an appropriate amount of high-purity quartz sand to be tested and melt it into a quartz crucible with a size of not less than 12 inches. First, cut off the transparent layer of the quartz crucible, grind and polish it to make a transparent sheet, and then test the bubble rate and light transmittance of the transparent sheet. For example, first use a diamond wire cutter to cut a thin slice from the inner wall of the quartz crucible, then use silicon carbide sandpaper to polish away the cutting marks step by step, and finally use cerium oxide polishing liquid to polish on a cloth disc until the surface is mirror smooth. S4. Establish a database of bubble density and light transmittance for inner, middle, and outer layer sands used in photovoltaic quartz crucibles. Compare the results measured in S3 with this database to finally determine the product grade of the high-purity quartz sand to be tested. By using S3 and S4, quality control is implemented at the product level, achieving a closed loop from raw materials to finished products.

[0008] This invention first determines the grade of the high-purity quartz sand to be tested based on three indicators: impurity elements, particle size distribution, and inclusion characteristics. Then, a glass melting test is used to further determine the grade. Finally, a small-sized quartz crucible is fabricated, and the grade is definitively determined through analysis of bubble density and transmittance. The rapid positioning method proposed in this invention covers high-purity quartz sand, quartz glass, and quartz crucible products, encompassing the entire quality evaluation chain from raw materials to semi-finished products and finished products. The positioning method is more comprehensive, objective, and accurate, and more importantly, it is low-cost, quick, and highly efficient.

[0009] Furthermore, in step S1, regarding impurity element indicators, the inner layer sand requires an Al content ≤15 μg / g, a sum of Li, Na, and K contents ≤1.5 μg / g, and a sum of Al, Fe, Ca, Mg, Ti, Cu, Co, Ni, Mn, Li, Na, K, B, Cr, Zr, Ba, and P contents ≤18 μg / g; the middle layer sand requires an Al content of 7-18 μg / g, a sum of Li, Na, and K contents ≤2.0 μg / g, and a sum of Al, Fe, Ca, Mg, Ti, Cu, Co, Ni, Mn, Li, Na, K, B, Cr, Zr, Ba, and P contents ≤25 μg / g; the outer layer sand requires… The required parameters are: Al content 12-20 μg / g; sum of Li, Na, and K content ≤ 2.5 μg / g; and sum of Al, Fe, Ca, Mg, Ti, Cu, Co, Ni, Mn, Li, Na, K, B, Cr, Zr, Ba, and P content ≤ 30 μg / g. Regarding particle size distribution, the mass percentage of 40-160 mesh particles should be ≥ 90% for inner, middle, and outer layer sands. Regarding inclusion characteristics, the mass percentage of pure inclusion particles should be ≥ 90% for inner layer sand, ≥ 80% for middle layer sand, and ≥ 70% for outer layer sand. Furthermore, in step S4, the inner layer sand requires: bubble density ≤ 60mm 2 Light transmittance ≥ 92%, middle layer sand requirement: 60mm 2 < Bubble density ≤ 150mm 2 Light transmittance ≤ 90% < 92%, outer sand layer requirement: 150mm 2 < Bubble density ≤ 800mm 2 80% ≤ light transmittance < 90%.

[0010] It should be noted that the standard databases for the three indicators of impurity elements, particle size distribution, and inclusion characteristics of the inner, middle, and outer sand layers used in photovoltaic quartz crucibles, as well as the databases for bubble density and light transmittance, are all based on the performance tests of a large number of high-purity quartz sands used in photovoltaic quartz crucibles collected by the inventors from the market.

[0011] Furthermore, in step S2, the amount of the high-purity quartz sand to be tested is 5-50g, and after ignition, it forms a glass body with a height of 5-8cm inside the high-purity quartz glass tube.

[0012] Furthermore, in step S2, the vacuuming time is 3-8 minutes to prevent impurities in the air, such as oxygen and water vapor, from reacting with the high-purity quartz sand to be tested at high temperatures, thus affecting the purity of the resulting glass.

[0013] Furthermore, in step S2, an oxyhydrogen flame is used for calcination for 8-15 minutes. Of course, other flames can also be used, such as a plasma flame. Both plasma and oxyhydrogen flames can melt the high-purity quartz sand into a glassy substance within minutes to tens of minutes, with the plasma flame being more stable. However, the oxyhydrogen flame is cheaper and more suitable for small-scale laboratory operations, while the plasma flame equipment is more expensive.

[0014] Furthermore, in step S3, in order to simulate the real production environment and save on the amount of raw materials used, 10-15 kg of the high-purity quartz sand to be tested is weighed and melted into a 12-inch quartz crucible.

[0015] Furthermore, in step S3, the thickness of the transparent sheet is 2±0.05mm.

[0016] In this technical solution, the thickness of the transparent sheet should not be too thin or too thick. If it is too thin, it is easy to deform during polishing, resulting in the illusion of bubbles. If it is too thick, it will reduce the light transmittance and cover up the real defects. Through several experiments, this invention has confirmed that the thickness of the transparent sheet should be controlled at 2 mm, and the thickness deviation should be controlled within ±0.05 mm.

[0017] Compared with existing technologies, the rapid positioning method proposed in this invention has low positioning cost, short time, and high efficiency, which plays a very positive role in breaking through the technical bottleneck of high-end quartz crucible preparation and improving the quality of basic materials in my country's photovoltaic industry chain. Moreover, compared with some judgment methods that only focus on the physical properties of high-purity quartz sand, this invention realizes the quality evaluation of the entire chain from raw materials to products, thus being more comprehensive, objective, and accurate. Attached Figure Description

[0018] Figure 1 Photograph of fluid inclusions in high-purity quartz sand in Example 1; Figure 2Comparison diagrams of the quartz glass prepared from high-purity quartz sand in Example 1 with the glass obtained from standard inner-layer quartz sand, standard middle-layer quartz sand, and standard outer-layer quartz sand: Figure A shows the glass prepared from high-purity quartz sand, and Figure B shows the glass obtained from standard inner-layer quartz sand, standard middle-layer quartz sand, and standard outer-layer quartz sand from left to right (labeled as inner-layer sand, middle-layer sand, and outer-layer sand in order). Figure 3 Photographs of the quartz crucible and transparent sheet prepared from the high-purity quartz sand in Example 1; Figure 4 Photograph of fluid inclusions in high-purity quartz sand in Example 2; Figure 5 The image shows a comparison between the quartz glass prepared from high-purity quartz sand in Example 2 and the glass obtained from standard inner-layer quartz sand, standard middle-layer quartz sand, and standard outer-layer quartz sand: Image A shows the glass prepared from high-purity quartz sand, and Image B shows the glass obtained from standard inner-layer quartz sand, standard middle-layer quartz sand, and standard outer-layer quartz sand, respectively, from left to right (labeled as inner-layer sand, middle-layer sand, and outer-layer sand in that order). Figure 6 Photographs of the quartz crucible and transparent sheet prepared from the high-purity quartz sand in Example 2; Figure 7 Photograph of fluid inclusions in high-purity quartz sand in Example 3; Figure 8 The image shows a comparison between the quartz glass prepared from high-purity quartz sand in Example 3 and the glass obtained from standard inner-layer quartz sand, standard middle-layer quartz sand, and standard outer-layer quartz sand: Image A shows the glass prepared from high-purity quartz sand, and Image B shows the glass obtained from standard inner-layer quartz sand, standard middle-layer quartz sand, and standard outer-layer quartz sand, respectively, from left to right (labeled as inner-layer sand, middle-layer sand, and outer-layer sand in that order). Figure 9 Photographs of the quartz crucible and transparent sheet prepared from the high-purity quartz sand in Example 3; Figure 10 The present invention is described in the following process flow. Detailed Implementation

[0019] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of this application.

[0020] It should be noted that: all technical solutions not described in detail below adopt conventional technical means in this field. All raw materials involved in the following embodiments and comparative examples are commercially available. All experimental equipment involved in the following embodiments and comparative examples are commercially available conventional experimental equipment in this field.

[0021] We purchased inner layer sand, middle layer sand, and outer layer sand for photovoltaic quartz crucibles through commercial channels, with no fewer than 15 samples of each type. By testing their bubble density and light transmittance, we summarized their threshold ranges and constructed a database of bubble density and light transmittance. Inner layer sand requirement: bubble density ≤ 60mm. 2 Light transmittance ≥ 92%, middle layer sand requirement: 60mm 2 < Bubble density ≤ 150mm 2 Light transmittance ≤ 90% < 92%, outer sand layer requirement: 150mm 2 < Bubble density ≤ 800mm 2 80% ≤ light transmittance < 90%.

[0022] A standard database summarizing the impurity elements, particle size distribution, and inclusion characteristics of the inner, middle, and outer layer sands used in photovoltaic quartz crucibles is established. This database is based on existing national standards (GB / T 45823-2025 "High-purity inner layer sand for photovoltaic monocrystalline silicon growth quartz crucibles", GB / T 32649-2016 "High-purity quartz sand for photovoltaics"), industry standards (JC / T 2531-2019 "Quartz crucibles for crystalline silicon growth"), and group standards (T / CEMIA 004-2018 "Quartz crucibles for photovoltaic monocrystalline silicon growth", T / TMAC 209-2025). The "Draft for Comments on Photovoltaic Grade High-Purity Quartz Sand" and, based on the test results of relevant indicators of existing high-purity quartz sand for photovoltaic crucibles on the market, the following impurity element indicators are proposed: For inner layer sand, Al content ≤ 15 μg / g, the sum of Li, Na, and K content ≤ 1.5 μg / g, and the sum of Al, Fe, Ca, Mg, Ti, Cu, Co, Ni, Mn, Li, Na, K, B, Cr, Zr, Ba, and P content ≤ 18 μg / g; for middle layer sand, Al content 7-18 μg / g, the sum of Li, Na, and K content ≤ 2.0 μg / g, and the sum of Al, Fe, Ca, Mg, Ti, Cu, Co, Ni, Mn, Li, Na, K, B, Cr, Zr, ... The sum of Ba and P content must be ≤25 μg / g; for outer layer sand, Al content must be 12-20 μg / g, the sum of Li, Na, and K content must be ≤2.5 μg / g, and the sum of Al, Fe, Ca, Mg, Ti, Cu, Co, Ni, Mn, Li, Na, K, B, Cr, Zr, Ba, and P content must be ≤30 μg / g; for particle size distribution, the mass percentage of 40-160 mesh particles must be ≥90% for inner, middle, and outer layer sands; for inclusion characteristics, the mass percentage of pure inclusion particles must be ≥90% for inner layer sand, ≥80% for middle layer sand, and ≥70% for outer layer sand.

[0023] Based on the two databases already constructed above, the following Examples 1-3 are presented.

[0024] Example 1 The following steps were followed to verify the location of an IOTA-CG high-purity quartz sand sample (labeled IOTA-CG) produced by Siliconware Precision Industries, Inc. S1. Impurity element and particle size analysis were performed on IOTA-CG, as shown in Table 1: The total of 17 impurity elements in IOTA-CG was 15.42 μg / g, the total of Li, Na, and K was 1.43 μg / g, and the Al content was 11.43 μg / g. The comparison shows that it meets the requirements for inner layer sand. As shown in Table 2: Its particle size is mainly concentrated in two sizes: -60 mesh +80 mesh and -80 mesh +100 mesh, that is, the +100 mesh content reaches 80.08%. Table 1. Impurity element analysis in IOTA-CG Table 2 IOTA-CG Particle Size Analysis A small amount of IOTA-CG was randomly selected and dispersed as evenly as possible on a glass slide. A coverslip was then placed on top, and oil was slowly dripped into the slide to prepare an oil-impregnated slide. The oil-impregnated slide was then observed under an optical microscope. The obtained fluid inclusions were as follows: Figure 1 As shown: the interior of the quartz sand particles is relatively clean overall, with a high percentage of pure particles. Some quartz sand particles show fluid inclusions distributed in bands and areas, and the percentage of pure particles is greater than 90%. S2. Weigh 10g of IOTA-CG and place it in a high-purity quartz glass tube. After evacuating for 3 minutes, ignite the quartz sand in the glass tube with an oxyhydrogen flame for 8 minutes. After cooling, a transparent glass body is obtained. Figure 2 As shown in Figure A: The glass obtained by IOTA-CG is generally transparent, with visible air bubbles of varying sizes dispersed within it; using the inner, middle, and outer layers of photovoltaic quartz crucible sand sold by Jiangsu Pacific Quartz Co., Ltd. as standard inner, middle, and outer quartz sands, the specific characteristics of the fused glass are as follows. Figure 2 As shown in Figure B, the comparison shows that the transparency of IOTA-CG meets the standards for inner sand. S3. Weigh 12 kg of IOTA-CG and distribute it evenly in the quartz crucible melting furnace mold. Melt a 12-inch quartz crucible using the electric arc method. Its appearance is as follows: Figure 3 As shown in Figure A; after the quartz crucible is removed and cooled, its transparent layer is cut, ground, and polished to produce a transparent sheet with a thickness of about 2mm, as shown. Figure 3 As shown in Figure B, the phenomena observed are largely consistent with those in photographs of molten transparent glass and fluid inclusions, exhibiting high transparency and sparsely dispersed bubbles. The bubble density and transmittance measurements are as follows: bubble density 32.66 mm. 2 Light transmittance: 92.29%; S4. Compare the test results of S3 with the database of bubble density and transmittance to confirm that it meets the requirements of photovoltaic-grade quartz crucible inner layer sand. Therefore, IOTA-CG can be used to prepare photovoltaic-grade quartz crucible inner layer sand.

[0025] Example 2 To locate a high-purity quartz sand sample (marked as self-made No. 1 sand), follow these steps: S1. Impurity element and particle size analysis were performed on the self-made No. 1 sand, as shown in Table 3. The total of 17 impurity elements in the self-made No. 1 sand was 16.95 μg / g, the total of Li, Na and K was 0.69 μg / g, and the Al content was 13.42 μg / g. The comparison shows that it meets the requirements of inner layer sand. As shown in Table 4, its particle size distribution is relatively wide, basically distributed between +60 mesh and -160 mesh. Table 3. Elemental analysis of impurities in self-made No. 1 sand Table 4 Particle size analysis of self-made No. 1 sand A small amount of homemade No. 1 sand was randomly selected and dispersed as evenly as possible on a glass slide. A coverslip was then placed on top, and oil was slowly dripped into the slide to prepare an oil-impregnated slide. The oil-impregnated slide was then observed under an optical microscope. The fluid inclusions obtained were as follows: Figure 4 As shown: the interior of the quartz sand particles is relatively clean overall, with a higher proportion of pure particles than impure particles. Some quartz sand particles show fluid inclusions distributed in bands, clusters, and planar patterns. Pure particles account for approximately 80%. S2. Weigh 12g of the self-made No. 1 sand and place it in a high-purity quartz glass tube. After evacuating the tube for 5 minutes, ignite the quartz sand in the glass tube with an oxyhydrogen flame for 12 minutes. After cooling, a transparent glass body is obtained. Figure 5 As shown in Figure A: The glass obtained from self-made No. 1 sand is relatively transparent overall, with densely packed, visible fine air bubbles dispersed within. Using the inner, middle, and outer layers of photovoltaic quartz crucible sand sold by Jiangsu Pacific Quartz Co., Ltd. as standard inner, middle, and outer layers of quartz sand, the specific details of the glass after melting are as follows. Figure 5 As shown in Figure B, the comparison shows that the transparency of the self-made No. 1 sand is lower than that of the standard inner layer quartz sand, but close to that of the standard middle layer quartz sand, which meets the standard for middle layer sand. S3. Weigh 13 kg of homemade No. 1 sand and distribute it evenly in the quartz crucible melting furnace mold. Melt a 12-inch quartz crucible using the electric arc method. Its appearance is as follows: Figure 6 As shown in Figure A; after the quartz crucible is removed and cooled, its transparent layer is cut, ground, and polished to produce a transparent sheet with a thickness of about 2mm, as shown. Figure 6As shown in Figure B, the phenomenon is consistent with that observed in photographs of molten transparent glass and fluid inclusions. The transparency is lower than that of the inner sand layer, and the bubbles are small and densely distributed. The bubble density and transmittance test results are: bubble density 105.86 mm. 2 Light transmittance: 91.12%; S4. Compare the test results of S3 with the database of bubble density and transmittance to confirm that it meets the requirements of the middle layer sand of photovoltaic-grade quartz crucible. Therefore, although the impurity element content of the self-made No. 1 sand meets the requirements of the inner layer sand, the transparency of the fluid inclusions and glass is poor, and it can be used as the middle layer sand for preparing photovoltaic-grade quartz crucible.

[0026] Example 3 The following steps are used to locate a high-purity quartz sand sample (marked as self-made No. 2 sand): S1. Impurity element and particle size analysis were performed on the self-made No. 2 sand, as shown in Table 5. The total of 17 impurity elements in the self-made No. 2 sand was 16.62 μg / g, the total of Li, Na, and K was 1.43 μg / g, and the Al content was 10.13 μg / g. The comparison shows that it meets the requirements of inner layer sand. As shown in Table 6, its particle size is mainly concentrated in three sizes: -80 mesh +100 mesh, -100 mesh +140 mesh, and -140 mesh +160 mesh. The content in these sizes can reach 85.18%. Table 5. Elemental analysis of impurities in self-made No. 2 sand Table 6. Particle size analysis of self-made No. 2 sand A small amount of homemade No. 2 sand was randomly selected and dispersed as evenly as possible on a glass slide. A coverslip was then placed on top, and oil was slowly dripped into the slide to prepare an oil-impregnated slide. The oil-impregnated slide was then observed under an optical microscope. The fluid inclusions obtained were as follows: Figure 7 As shown: the interior of the quartz sand particles is relatively clean overall, with a high percentage of pure particles. Some quartz sand particles show fluid inclusions distributed in bands and planar patterns. The percentage of pure particles is approximately 95%. S2. Weigh 15g of homemade No. 2 sand and place it in a high-purity quartz glass tube. After evacuating the tube for 8 minutes, ignite the quartz sand in the glass tube using an oxyhydrogen flame for 15 minutes. After cooling, a transparent glass body is obtained. Figure 8 As shown in Figure A: The glass obtained from the self-made No. 2 sand has high overall transparency, with sparsely distributed bubbles of varying sizes inside; using the inner, middle, and outer layers of photovoltaic quartz crucible sand sold by Jiangsu Pacific Quartz Co., Ltd. as standard inner, middle, and outer layers of quartz sand, the specific details of the glass after melting are as follows. Figure 8 As shown in Figure B, the transparency of the self-made No. 2 sand is close to that of the inner layer sand. S3. Weigh 15 kg of homemade No. 2 sand and distribute it evenly in the quartz crucible melting furnace mold. Melt a 12-inch quartz crucible using the electric arc method. Its appearance is as follows: Figure 9 As shown in Figure A; after the quartz crucible is removed and cooled, its transparent layer is cut, ground, and polished to produce a transparent sheet with a thickness of about 2mm, as shown. Figure 9 As shown in Figure B, the phenomenon is consistent with that observed in photographs of molten transparent glass and fluid inclusions, exhibiting high transparency and sparsely dispersed bubbles. The bubble density and transmittance measurements are as follows: bubble density 36.32 mm. 2 Light transmittance: 92.75%; S4. Compare the test results of S3 with the database of bubble degree and light transmittance to confirm that it meets the requirements of photovoltaic-grade quartz crucible inner layer sand. Therefore, the self-made No. 2 sand can be used to prepare photovoltaic-grade quartz crucible inner layer sand.

[0027] Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make modifications, alterations, substitutions, and variations to the above embodiments within the scope of the present invention. Furthermore, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of the different embodiments or examples.

Claims

1. A rapid positioning method for high-purity quartz sand used in photovoltaic quartz crucibles, characterized in that, The following steps are included: S1. Establish a standard database of three indicators for the inner layer sand, middle layer sand and outer layer sand of photovoltaic quartz crucible: impurity elements, particle size distribution and inclusion characteristics. Test these three indicators of the high-purity quartz sand to be tested. By comparing with the standard database, the position of the high-purity quartz sand to be tested can be preliminarily determined. S2. Weigh an appropriate amount of the high-purity quartz sand to be tested and place it in a high-purity quartz glass tube. After evacuating the tube, ignite the high-purity quartz sand to be tested so that the bottom melts into a glass body. After cooling, observe the transparency of the glass body and compare it with the glass bodies obtained by igniting the standard inner layer quartz sand, standard middle layer quartz sand, and standard outer layer quartz sand respectively using the above method. Based on the principle of similar transparency, re-determine the position of the high-purity quartz sand to be tested. S3. Weigh an appropriate amount of high-purity quartz sand to be tested and melt it into a quartz crucible with a size of not less than 12 inches. First, cut off the transparent layer of the quartz crucible, grind and polish it to make a transparent sheet, and then test the bubble rate and light transmittance of the transparent sheet. S4. Establish a database of bubble density and light transmittance for inner, middle, and outer layer sands used in photovoltaic quartz crucibles. Compare the results measured in S3 with this database to finally determine the product grade of the high-purity quartz sand to be tested.

2. The rapid positioning method for high-purity quartz sand used in photovoltaic quartz crucibles according to claim 1, characterized in that, In step S1, regarding impurity element indicators, the inner layer sand requires an Al content ≤15 μg / g, a sum of Li, Na, and K contents ≤1.5 μg / g, and a sum of Al, Fe, Ca, Mg, Ti, Cu, Co, Ni, Mn, Li, Na, K, B, Cr, Zr, Ba, and P contents ≤18 μg / g; the middle layer sand requires an Al content of 7-18 μg / g, a sum of Li, Na, and K contents ≤2.0 μg / g, and a sum of Al, Fe, Ca, Mg, Ti, Cu, Co, Ni, Mn, Li, Na, K, B, Cr, Zr, Ba, and P contents ≤25 μg / g; the outer layer sand requires an Al content of ≤15 μg / g. The content of Li, Na, and K should be 12-20 μg / g, with the sum of their contents ≤2.5 μg / g and the sum of their contents ≤30 μg / g. Regarding particle size distribution, the inner, middle, and outer sand layers should all have a particle size distribution of ≥90% by mass for particles of 40-160 mesh. Regarding inclusion characteristics, the inner sand layer should have a pure particle size distribution of ≥90% by mass for pure inclusion particles, the middle sand layer should have a pure particle size distribution of ≥80% by mass for pure inclusion particles, and the outer sand layer should have a pure particle size distribution of ≥70% by mass for pure inclusion particles.

3. The rapid positioning method for high-purity quartz sand used in photovoltaic quartz crucibles according to claim 1, characterized in that, In step S4, the inner layer sand requires: bubble density ≤ 60mm 2 Light transmittance ≥ 92%, middle layer sand requirement: 60mm 2 < Bubble density ≤ 150mm 2 Light transmittance ≤ 90% < 92%, outer sand layer requirement: 150mm 2 < Bubble density ≤ 800mm 2 80% ≤ light transmittance < 90%.

4. The rapid positioning method for high-purity quartz sand used in photovoltaic quartz crucibles according to claim 1, characterized in that, In step S2, the amount of high-purity quartz sand to be tested is 5-50g, and after ignition, it forms a glass body with a height of 5-8cm inside the high-purity quartz glass tube.

5. The rapid positioning method for high-purity quartz sand used in photovoltaic quartz crucibles according to claim 1, characterized in that, In step S2, the vacuuming time is 3-8 minutes.

6. The rapid positioning method for high-purity quartz sand used in photovoltaic quartz crucibles according to claim 1, characterized in that, In step S2, an oxyhydrogen flame is used for calcination for 8-15 minutes.

7. The rapid positioning method for high-purity quartz sand used in photovoltaic quartz crucibles according to claim 1, characterized in that, In step S3, 10-15 kg of the high-purity quartz sand to be tested is weighed and melted into a 12-inch quartz crucible.

8. The rapid positioning method for high-purity quartz sand used in photovoltaic quartz crucibles according to claim 1, characterized in that, In step S3, the thickness of the transparent sheet is 2±0.05mm.